A Method for the Isolation of Exosomes from Human and Bovine Milk. (3rd December 2019) - Vaswani, Kanchan; Mitchell, Murray D.; Holland, Olivia J.; Qin Koh, Yong; Hill, Rebecca J.; Harb, Tracy; Davies, Peter S. W.; Peiris, Hassendrini
Abstract : Scope . Milk provides a natural means of nutrient supply to infants. Exosomes are an important component of milk that are not only being studied for their promise in translational medicine but also in infant nutrition. They also play important roles in intercellular communication and immune function in mammary glands and are able to transfer their materials to the recipient. Therefore, the isolation of high-quality exosomes is an important aspect of exosome research. Methods and Results . This study is a technical study, which provides a detailed methodology for the isolation and enrichment of exosomes from milk. In this study, we evaluate the suitability of using the exosome enrichment method that we have recently published for bovine milk, on human milk. We initially isolated extracellular vesicles from human and bovine milk on a fresh set of samples, using ultracentrifugation, and then exosomes were subsequently enriched via size exclusion chromatography (SEC). Following isolation and enrichment, exosomes from both species were characterized by particle concentration (nanoparticle tracking analysis, NTA), morphology (transmission electron microscopy, TEM), and the presence of exosomal markers (immunoblotting and mass spectrometry using information dependant acquisition (IDA)). The key exosomal characteristics of spherical/donut-shaped morphology, the presence of exosomal markers, e.g., FLOT-1 and the tetraspanins, CD9 and CD81), and particle concentration were confirmed in both human and bovine milk exosomes. Conclusion . We conclude that our robust exosome enrichment method, previously published for bovine milk, is suitable for use on human milk.